Suffering, Monstrosity, Exceptionality - Briggs, Robert (Palgrave MacMillan, 2025)
In what sense — which is to say, in what forms, under what conditions, and via what mechanisms — can nonhuman beings and forces take the form or play the part of political agency? While much recent work in the fields of posthumanism, animal studies and environmental humanities has helped to highlight, against the prevailing anthropocentric prejudice, the agential power of various nonhuman beings and conditions, the specifically political dimension to that agency is often obscure and frequently assumed. This chapter sets out to explore this problematic through an analysis of diverse sites and scenes of environmental politics. In the first instance, the analysis turns on the extent to which those cases articulating the most immediately available languages and frameworks for imagining environmental politics remain delimited by the anthropocentric nature of politics-as-usual insofar as they render nonhuman entities as the passive target of anthropic violence, governmental processes and representational politics. Drawing on a broadly continental tradition of philosophical inquiry, the discussion goes on to supplement this critical reading with a speculation on the potential for more-than-human forms of agency to appear otherwise within the space of politics today.